SMED Simulation in Optimising the Operating Output of Tandem Press Line in the Automotive Industry using WITNESS Software - Azizul Qayyum, Basri; N. M. Zuki, N. M.; Nelfiyanti, Nelfiyanti; Yusrizal, Yusoof (Universiti Malaysia Pahang, 2021)
The automotive industry is one of the most advanced industries in the world. The demand for vehicles keeps increasing over time, mainly influenced by technology’s sophistication and impressive designs. This research is focusing on the production performance of the stamping process in Malaysia’s automotive industry. The main issue observed and evidenced in data collected from industry players is that an unacceptably long time is taken in the die/tooling change process, which grossly affects the planned production output. The most significant direct impact on this situation is the increase in operating costs due to additional time taken to meet the planned production output. Therefore, this research aims to establish a new framework that can optimise the efficiency of the dies changeover process, which could lower the overall production cost, which could partially transfer the saving to the consumers. The study was conducted in two stages; the first is on data collection correlates with the automotive stamping premise to create a simulation procedure, and the second is to analyse the current production output using WITNESS simulation. These simulated output data have later been compared to the actual industrial data. Using a systematic dies changeover process, a new alternative framework was proposed. The framework combined single minute exchange of die (SMED), lean tools and simulation to become an integrated single minute exchange of die (ISMED). It shows that the proposed method decreased the changeovers processes from the initial of 1509.5 seconds to 750.75 seconds, then further reduced to 569.75 seconds, with the nett time reduction of 62.2%. The result shows that the daily production output has increased gradually from 1100 pieces to 1500 pieces, further increasing to 2145 pieces. As evidenced in analytical data, it is believed that this new framework can strengthen the total output in the manufacturing process, especially in the manufacturing of automotive stamping parts.